Joint moments of unilateral transfemoral amputees using running-specific prosthesis during sprinting - Namiki, Y.; Sano, Y.; Makimoto, A.; Hashizume, S.; Murai, A.; Kobayashi, Y.; Takemura, H.; Hobara, H. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to investigate the bilateral difference of the joint moments between an intact leg (INT) and a prosthetic leg (PST) in unilateral transfemoral amputees (TFAs) wearing running-specific prosthesis during sprinting. Eight sprinters with unilateral TFAs performed maximal sprinting on a 40-m runway with 7 force platforms located in between. Hip and knee joint extension and flexion moments during stance phase in INT were significantly greater than those of PST. However, ankle plantarflexion moment in PST was significantly greater than that of INT. Since kinetic asymmetry between legs is thought to be related with running-related injury, sprinter with unilateral TFAs may have a higher risk of musculoskeletal injury at hip and knee joints.